Development of low-cost formulations of plant growth-promoting bacteria to be used as inoculants in beneficial agricultural technologies - Lobo, Constanza Belén (2018)
Phosphorus is one of the main macronutrients for plant development. Despite its large deposits in soils, it is scarcely available for plants. Phosphate-solubilizing bacteria, belonging to the group of plant growth-promoting rhizobacteria (PGPR), are capable of mobilizing deposits of insoluble phosphates in the soil. The use of PGPR as inoculants provides an environmentally sustainable approach to increase crop production. The effectiveness of inoculants depends on their proper production, formulation and storage in order to ensure the application of the required number of viable microbial cells. In order to develop inexpensive technology, low-cost compounds for biomass production and protection should be used. After the biomass production process, the product should be formulated in a liquid or a solid form, taking into account required storage time, use of protectors/carriers, storage conditions (temperature, humidity, etc.), ease of application and maintenance of beneficial effects on crops. Careful determination of these optimal conditions would ensure a low-cost efficient inoculant that would promote the growth and yield of various crops.